Immunotherapy of medullary thyroid carcinoma (Contemporary Oncology/Współczesna Onkologia, 2005)
Medullary Thyroid Carcinoma (MTC) accounts 5-10% of all thyroid carcinoma. In therapy, the standard procedure is total thyroidectomy and central lymph node dissection. Radioiodine therapy and both chemo and radiotherapy appear to be of a little therapeutic value. This survey describes most therapeutic methods, both experimental and clinical, applied in the MTC therapy. Expression of many target antigens like calcitonin, carcinoembryonic antigen (CEA), Chromogranin A, ACTH, somatostatin, cancer/testis antigens (CTA) and lately ghrelin were observed in MTC. The most frequent application in the diagnosis and treatment of MTC is radiolabeled monoclonal antibodies against CEA. Pronounced CEA elevation appear to be prognostically more reliable in patients with metastatic disease and aggressive tumor. The presence of cholecystokinin CCK-B/gastrin receptors is more than 90% of MTC tumors. On this basis introductory experimental research with the use of human gastrin was carried out. An attempt was made to apply monoclonal antibodies against rat calcitonin the majority of which was inactive and only few hampered the growth of rat MTC cells in vitro. In order to obtain better immunological response dendritic cells were used. DNA immunization with human preprocalcitonin activates the specific cell and humoral immune response. In the MTC therapy interleukins 2 and 12 were used. Also, an attempt was made to implement and afflict the MTC cells with adenovirus and next take up ganciclovir therapy. 131 I-MIBG is used in 35-40% of MTC cases with marker uptake. Somatostatin is mainly used to inhibit secretory activity of the hormone producing tumors. Unfortunately none of the described methods brought about a decisive improvement in the MTC therapy.